Keraton Yogyakarta dan Praktik Literasi Budaya Keagamaan Melalui Media Digital - Iswanto, Agus (Jurnal Lektur Keagamaan, 2019)
Cultural literacy is important because of the diversity of Indonesian culture, and the challenges of globalization and the digital revolution. Cultural literacy can be done through various media and institutions, but there are not many institutions and media care to this cultural literacy. Yogyakarta Palace is one of the traditional institutions that practice cultural literacy through digital media. This article aims to identify the types of digital media that are used as a vehicle for literacy practices in Islamic religious culture, describe the Islamic religious culture that is displayed and interpret aspects of Islamic religious teachings of the religious culture. In addition, this article discusses the negotiation and adaptation of the Yogyakarta Palace in the practice of literacy through digital media. This study found that, in addition to education about the treasures of Islamic religious culture, the practice of literacy of Islamic religious culture through digital media carried out by the Yogyakarta Palace also showed negotiations and adaptations. Negotiations and adaptations arise in two ways. The first is negotiation and adaptation of tradition with digital technology, namely the Yogyakarta Palace presenting traditional culture (including religious culture) in digital space. Second, negotiation and adaptation of Javanese Islamic identity to the understanding of Islam that does not accept cultural elements in practicing Islamic teachings.Keywords: Literacy practice, religious cultural literacy, digital media, Yogyakarta PalaceÂ Literasi budaya penting karena keragaman budaya Indonesia serta tantangan globalisasi dan revolusi digital. Literasi budaya dapat dilakukan melalui berbagai media dan institusi, tetapi tidak banyak institusi dan media yang memperhatikan literasi budaya ini. Keraton Yogyakarta adalah salah satu institusi tradisional yang mempraktikkan literasi budaya melalui media digital. Artikel ini bertujuan untuk mengidentifikasi jenis-jenis media digital yang digunakan sebagai wahana praktik literasi dalam budaya agama Islam, menggambarkan budaya agama Islam yang ditampilkan dan menafsirkan aspek-aspek ajaran agama Islam dari budaya agama. Selain itu, artikel ini membahas negosiasi dan adaptasi Keraton Yogyakarta dalam praktik literasi melalui media digital. Studi ini menemukan bahwa, selain pendidikan tentang khazanah budaya agama Islam, praktik literasi budaya agama Islam melalui media digital yang dilakukan oleh Istana Yogyakarta juga menunjukkan negosiasi dan adaptasi. Negosiasi dan adaptasi muncul dalam dua cara. Pertama adalah negosiasi dan adaptasi tradisi dengan teknologi digital, yaitu Keraton Yogyakarta menghadirkan budaya tradisional (termasuk budaya agama) di ruang digital. Kedua, negoÂsiasi dan adaptasi identitas Islam Jawa dengan pemahaman Islam yang tidak menerima unsur budaya dalam mempraktikkan ajaran Islam.Kata Kunci: Praktik literasi, literasi budaya keagamaan, media digital, Keraton Yogyakarta